The Impact of Combining Nutrition Education with Active Choice on the Fruit and Vegetable Consumption Among Second Grade Students - M. Cafiero, Robyn; Bai, Yeon; Feldman, Charles; Liou, Doreen (International Journal of Nutrition, 2020)
Daily intake of fruits and vegetables provides the basis for healthy nutrition. Yet low consumption of fruits and vegetables (FV) persists among school-aged children. Framed by the Social Cognitive Theory, this study aimed to determine the effectiveness of nutrition lessons combined with an active choice intervention on children’s FV consumption. Using a quasi-experimental design, 89 second graders were assigned to groups. Students in the experimental group (n=46) received four nutrition lessons combined with nine active choice sessions, while those in the control group (n=43) received active choice sessions only. Responses to pre- and post-intervention surveys that inquired FV knowledge and consumption were compared within and between groups using independent and paired t-tests. Empowered by improved knowledge, self-efficacy and the positive environment created through nutrition lessons and active choice, the experimental group showed improvement in consumption behavior compared to the control group at post-intervention: bringing FV to school and finish eating (69.7 vs. 51.2, p=.05 for fruits; 43.5 vs. 39.5, p=.41 for vegetables); like choosing FV (84.8 vs. 65.1, p=.01); like to eat more FV (80.4 vs. 62.8, p=.16); FV are healthy (100 vs. 95.3, p=.14). The magnitude of improvement is small yet consistent in every aspect of outcome measures. Combining nutrition education with the active choice component showed potential for a larger impact on behavior change among study participants. Parental support and community involvement could enhance the effectiveness of nutrition education in schools.
Keywords: Fruits and vegetable consumption; nutrition education; social cognitive theory; active choice